The Effect of Training and Empowerment on the Performance of Supporting Officers for Increasing the Agricultural Economy at the Agricultural Extension Training Center in South Sumatra Province - Verawati Saputra; Yunita Sari; Rini Efrianti. (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2023)
This study aims to analyze the effect of training and empowerment on the performance of assistant officers for improving the agricultural economy at the Agricultural Extension Training Center (BPPP) of South Sumatra Province in East OKU Regency, either partially or simultaneously. The type of research used in this study is a quantitative descriptive method. The data analysis is multiple regression analysis. The results of the study show that this research empirically proves that training and empowerment have a significant effect on the performance of Agricultural Economic Improvement Assistance Officers at the Agricultural Extension Training Center (BPPP). South Sumatra in East OKU Regency. The magnitude of the influence of training and empowerment on the performance of Agricultural Economic Improvement Assistance Officers is 87.5%, while other variables determine the remaining 12.5%. Training and empowerment policies significantly affect the performance of Agricultural Economic Improvement Assistance Officers because good performance greatly supports increased agricultural production and productivity, specifically in the District. East OKU and, in general, in the province of South Sumatra.